2015
DOI: 10.1099/jgv.0.000232
|View full text |Cite
|
Sign up to set email alerts
|

PA-X is a virulence factor in avian H9N2 influenza virus

Abstract: H9N2 influenza viruses have been circulating worldwide in multiple avian species, and regularly infect pigs and humans. Recently, a novel protein, PA-X, produced from the PA gene by ribosomal frameshifting, was demonstrated to be an antivirulence factor in pandemic 2009 H1N1, highly pathogenic avian H5N1 and 1918 H1N1 viruses. However, a similar role of PA-X in the prevalent H9N2 avian influenza viruses has not been established. In this study, we compared the virulence and cytopathogenicity of H9N2 WT virus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 22 publications
7
70
1
Order By: Relevance
“…9 and Table 1). These data are consistent with previous findings describing that a pH1N1 WT virus showed a slightly increased virulence in mice compared to a virus expressing lower levels of the PA-X protein (21,35). Remarkably, by using our pH1N1 LAIV virus, we have observed greater differences in virus pathogenicity than those observed using pH1N1 WT, suggesting that the LAIV virus backbone is better suited to detect differences in pathogenicity than the WT backbone.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…9 and Table 1). These data are consistent with previous findings describing that a pH1N1 WT virus showed a slightly increased virulence in mice compared to a virus expressing lower levels of the PA-X protein (21,35). Remarkably, by using our pH1N1 LAIV virus, we have observed greater differences in virus pathogenicity than those observed using pH1N1 WT, suggesting that the LAIV virus backbone is better suited to detect differences in pathogenicity than the WT backbone.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, Gao et al (43) and Hu et al (16) reported that loss of PA-X expression increased viral replication and pathogenicity of pH1N1 and H5N1 IAVs. In contrast, recent work has described that loss of PA-X in pH1N1 or H9N2 viruses leads to a reduction in viral pathogenicity (21,35). In addition, IAV strain-specific differences in the ability to block the cellular protein synthesis have also been reported (25,(31)(32)(33).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Several previous reports have examined the effects of PA-X on host response by comparing wild type and mutant virus infections, and shown that PA-X was important for modulating various immune responses (2, 68, 12, 14). To further elucidate PA-X’s effects on the host, we transfected plasmids expressing only PA-X into cell cultures and used RNA-seq to analyze the transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…This ribonuclease domain has been attributed to the N terminal region, although several recent publications have shown that the C-terminal region may also be important in regulating ribonuclease activity (10, 12, 13). Interestingly, PA-X has also been shown to modulate other virus-host interactions such as preventing stress granule formation (and thereby preventing translational arrest), increasing the accumulation of poly(A)-binding proteins within the nucleus, and exhibiting anti-apoptotic activity (5, 6, 14). …”
Section: Introductionmentioning
confidence: 99%